2003
DOI: 10.1093/jn/133.3.895s
|View full text |Cite
|
Sign up to set email alerts
|

Markers of the Validity of Reported Energy Intake

Abstract: Energy intake (EI) is the foundation of the diet, because all other nutrients must be provided within the quantity of food needed to fulfill the energy requirement. Thus if total EI is underestimated, it is probable that the intakes of other nutrients are also underestimated. Under conditions of weight stability, EI equals energy expenditure (EE). Because at the group level weight may be regarded as stable in the timescale of a dietary assessment, the validity of reported EI can be evaluated by comparing it wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

67
865
14
16

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 900 publications
(962 citation statements)
references
References 143 publications
67
865
14
16
Order By: Relevance
“…Some reasons that our findings conflict with those of previous studies are that we took into account all eating occasions at one time in our statistical models, and we excluded subjects with physiologically implausible reports of energy intake from our analysis. 22 It has been demonstrated unequivocally that overweight and obese subjects are more likely to provide physiologically implausible reports of energy intake than normal weight subjects, 23,24,41,65,66 typically under-reporting energy intake by 30-50%. Older persons may also under-report energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…Some reasons that our findings conflict with those of previous studies are that we took into account all eating occasions at one time in our statistical models, and we excluded subjects with physiologically implausible reports of energy intake from our analysis. 22 It has been demonstrated unequivocally that overweight and obese subjects are more likely to provide physiologically implausible reports of energy intake than normal weight subjects, 23,24,41,65,66 typically under-reporting energy intake by 30-50%. Older persons may also under-report energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…To minimise the influence of dietary underreporting, we used energy-adjusted values. Studies have consistently shown that underreporting is more prevalent among people with higher BMI 30,31 , and that energydense, nutrient-dilute and low-cost foods such as fat and oils, sugar and confectioneries are more likely to be selectively underreported 30,32 . However, as mentioned above, exclusion of energy underreporters identified by the Goldberg cut-off method 21,23 did not change the results materially, which may support the robustness of the findings in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary assessment questionnaires have been developed for assessing habitual dietary intake and for ranking subjects according to their dietary intake. However, they cannot entirely avoid reporting errors (Barrett-Connor, 1991), including not only random but also systematic errors (Black and Cole, 2001;Livingstone and Black, 2003), due to the fact that they are self-reported.…”
Section: Introductionmentioning
confidence: 99%